Pemanfaatan Fatiando a Terra untuk Analisis Data Gravitasi GGMplus berbasis Pustaka Python - Mardiyanto; Amelia, Tri; Sunardi, Bambang; Prayoedhie, Setyoajie (Jurnal Stasiun Geofisika Sleman, 2023)
The gravity method is one of the methods that can be used for regional geological studies according to differences in rock density due to variations in the Earth's gravitational field. Gravity data is not limited to field data but can also use satellite data such as GGMplus. The interpretation of gravity data in this paper is based on the results of regional anomalies and residual anomalies in the research area. Initially, the data was processed using the python verde, harmonica, boule, and pooch libraries by Fatiando a terra. The results of processing GGMplus gravity data using the python library by Fatiando a Terra indicate regional anomaly values ranging from 60 mGal to 130 mGal whereas the residual anomaly is between -30 mGal to 30 mGal. Synchronization between the position of positive and negative values of the residual anomaly and the fault coordinates coincide so that the faults in the Special Region of Yogyakarta are identified.